Desain Kelas Luar Ruangan yang Aktif dan Inovatif di Universitas Multimedia Nusantara Tangerang - Pranata, Hedista Rani; Angraini, Devi (Universitas muhammadiyah palembang, 2023)
Since the beginning of creation, humans have lived in nature and evolved through coexistence. The natural ecosystem has directly contributed to human development, satisfying basic and spiritual needs, and sustaining life. Therefore, exposure and direct experience with nature are crucial in all aspects of life, including education. Several studies have examined the impact of outdoor learning activities, both in general and at the university level. Learning outdoors can improve focus, trigger diverse ideas and responses, and enhance understanding of natural and social phenomena. There are six main aspects to consider in the design of outdoor classrooms: flexibility and adaptability, comfort and safety, sustainability, aesthetics, accessibility, and technology. Those six aspects were then applied to the design framework of the outdoor classroom at Multimedia Nusantara University as pilot project, which is flexible and open to future changes or additions.